Application and Theory of Multimedia Signal Processing Using Machine Learning or Advanced Methods - Kim, Cheonshik (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue is a book composed by collecting documents published through peer review on the research of various advanced technologies related to applications and theories of signal processing for multimedia systems using ML or advanced methods. Multimedia signals include image, video, audio, character recognition and optimization of communication channels for networks. The specific contents included in this book are data hiding, encryption, object detection, image classification, and character recognition. Academics and colleagues who are interested in these topics will find it interesting to read.